Factors Influencing Malnutrition of Children Aged 24-60 Months Old in Flores Timur, Nusa Tenggara Timur - Betan, Yasinta; Hemchayat, Monthana; Wetasin, Kanokwan (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2022)
Malnutrition remains a global health problem, especially in developing countries such as Indonesia. This study aimed to determine factors influencing the nutritional status of children aged 24-60 months in rural communities of Flores Timur, Nusa Tenggara Timur. A cross-sectional design involving purposeful sampling was used to conduct a study in five rural villages. The sample size for the study involved 250 mothers with children aged between 24-60 months. Data collection was conducted using questionnaires with information regarding socio-demographic, dietary intakes, diseases, child care practices, and anthropometric measurement. Furthermore, a multivariate binary logistic regression was employed for the data analysis. Results from binary logistic regression revealed that energy intake (OR=8.99), protein intake (OR=6.95), the occurrence of infectious diseases (OR=6.45), the frequency of infectious diseases (OR=6.00), and age of introduction of complementary foods (OR=34.55) significantly influenced nutritional status in rural communities. Based on these findings, health workers should promote the appropriate time for giving complementary foods to children. Moreover, interventions should be made for children with an acute respiratory infection and/or diarrhea over the past six months to maintain nutritional status.